Peranan Financial Performance Memoderasi Hubungan Penerapan Green Accounting dan Corporate Social Responsibility Dengan Firm Value - Ita Darsita (Excellent, 2025)
This research explains the phenomenon of factors that influence company value. Company value is very important because it will affect the company's image. The better the company's image, the more it will influence investors' confidence in making investments. Based on related phenomena and theories, the factors that influence company value in this research are the implementation of green accounting and corporate social responsibility. A company's success is often directly related to rising stock prices. Companies that have good value tend to have high share prices, both short and long term. This research aims to examine and analyze the moderating role of financial performance in the influence of the implementation of green accounting and corporate social responsibility on firm value in energy companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The type of research used is associative quantitative research. This research uses secondary data, a population of 82 energy companies listed on the Indonesia Stock Exchange from 2018-2022, the sampling method used a random  sampling technique to obtain 13 companies as research samples. The data analysis method used is a panel data regression test using Microsoft Excel and Eviews 12 applications. The research results show that green accounting and corporate social responsibility have a positive effect on firm value. Partially, green accounting has a negative effect on firm value, while corporate social responsibility has a positive effect on firm value. Financial performance can moderate the relationship between green accounting and corporate social responsibility on firm value.